Predictors of mortality and outcomes in transvenous lead extraction for systemic and local infection cohorts. Issue 1 (20th November 2018) - Gould, Justin; Klis, Magdalena; Porter, Bradley; Sidhu, Baldeep S.; Sieniewicz, Benjamin J.; Williams, Steven E.; Teall, Thomas; Webb, Jessica; Shetty, Anoop; Gill, Jaswinder; Rinaldi, Christopher A.
Abstract: Background: Transvenous lead extraction (TLE) may be necessary due to infective and noninfective indications. We aim to identify predictors of 30‐day mortality and risk factors between infective versus noninfective groups and systemic versus local infection subgroups. Methods: A total of 925 TLEs between October 2000 and December 2016 were prospectively collected and dichotomized (infective group n = 505 vs noninfective group n = 420 and systemic infection n = 164 vs local infection n = 341). Results: All‐cause major complication including deaths was significantly higher (5.1%, n = 26 vs 1.2%, n = 5, P = 0.001) as well as 30‐day mortality (4.0%, n = 20 vs 0.2%, n = 1, P < 0.001) in the infective group compared to the noninfective group. Both subgroups (systemic vs local infection) were balanced for demographics. All‐cause major complication including deaths was significantly higher (9.1%, n = 15 vs 3.2%, n = 11, P = 0.008) as well as all‐cause 30‐day mortality (7.9%, n = 13 vs 2.1%, n = 7, P = 0.003) in the systemic infection subgroup compared to the local infection subgroup. Conclusion: Patients undergoing TLE for infective indications are at greater risk of 30‐day all‐cause mortality compared to noninfective patients. Patients undergoing TLE for systemic infective indications are at greater risk of 30‐day all‐cause mortality compared to patients with local infection. Renal impairment, systemic infection, and elevated preprocedure C‐reactive protein are independent predictors of 30‐day all‐cause mortality in patients undergoing TLE for an infective indication.